Perceived neighbourhood environmental attributes associated with adults׳ recreational walking: IPEN Adult study in 12 countries - Sugiyama, Takemi; Cerin, Ester; Owen, Neville; Oyeyemi, Adewale L; Conway, Terry L; Van Dyck, Delfien; Schipperijn, Jasper; Macfarlane, Duncan J; Salvo, Deborah; Reis, Rodrigo S; Mitáš, Josef; Sarmiento, Olga L; et al. (Health & place, 2014)
This study examined the strength and shape of associations between perceived environmental attributes and adults' recreational walking, using data collected from 13,745 adult participants in 12 countries. Perceived residential density, land use mix, street connectivity, aesthetics, safety from crime, and proximity to parks were linearly associated with recreational walking, while curvilinear associations were found for residential density, land use mix, and aesthetics. The observed associations were consistent across countries, except for aesthetics. Using data collected from environmentally diverse countries, this study confirmed findings from prior single-country studies. Present findings suggest that similar environmental attributes are associated with recreational walking internationally.
Keywords: Cross-Cultural Comparison; Female; Urban Population; lidé středního věku; estetika; charakteristiky bydlení; Exercise; Austrálie; průzkumy a dotazníky; Cross-Sectional Studies; regresní analýza; Leisure; South America; Adolescent; Residence Characteristics; Walking; mužské pohlaví; městské obyvatelstvo; New Zealand; mladý dospělý; Humans; Urban design; Environment Design; dospělí; Spojené státy americké; Europe; Mexico; Hongkong; Nový Zéland; Esthetics; průřezové studie; Hong Kong; Australia; Jižní Amerika; Perception; Evropa; lidé; chůze; Middle Aged; Regression Analysis; Surveys and Questionnaires; srovnání kultur; senioři; Recreation; United States; Built environment; společenská třída; ženské pohlaví; rekreace; Physical activity; Mexiko; Aged; Young Adult; Social Class; percepce; Adult; životní prostředí - projekt; Male; mladiství